Changing standards in the treatment of desmoid tumors?. (November 2017) - Trippel, A; Cathomas, R; Michelitsch, C; Furrer, M
Abstract : Objectives: Desmoid Tumors (DT) are rare locally aggressive and never metastasizing mesenchymal tumors. They usually grow slowly and often present on the trunk or extremity, on the abdominal wall or intra-abdominally. Radical surgical removal has been considered the treatment of choice for many years, although high recurrence rates ranging from 30% to 40% have been reported. Methods: A 40-year old woman was referred to our department with a 4cmx2cmx3cm painless hard tumor on the lateral wall of the right thorax. A histological diagnosis of a DT was made after a biopsy specimen was obtained. After initial R0 surgical resection the patient developed a chronic pain syndrome. Another surgical R0 resection was performed after local recurrence was noted in an MRI fifteen months postoperative. 30 months after the first operation and 17 months after the second operation a second local recurrence was seen. A third operation was planned but the patient chose not to undergo surgery and was referred to the medical oncologist. A therapy with tamoxifen was started and supplemented with sulindac after two months since a tumor progression was shown in the first follow up MRI. Results: The follow up under the tamoxifen/sulindac therapy showed disease stabilization after 12 months and a complete tumor regression after 1½ years. The tamoxifen/sulindac regimen and the follow-up were continued, and the patient is now tumor free after 3½ years of medical treatment. The pain syndrome has also improved although the patient is still under oxycodone therapy. Conclusions: In current practice, the treatment of desmoid tumor medical therapy was reserved to unresectable disease or where radical resection would have brought to major functional or cosmetic losses. This present case calls into question the established surgical therapy of desmoid tumors. Although a strong evidence-based treatment is still missing, other recent studies have also suggested alternative different therapeutic strategies based on a "wait and see" strategy may be effective in the case of asymptomatic disease.